The α-Crystallin Domain Containing Genes: Identification, Phylogeny and Expression Profiling in Abiotic Stress, Phytohormone Response and Development in Tomato (Solanum lycopersicum) - Paul, Asosii; Rao, Sombir; Mathur, Saloni (Frontiers in Plant Science, 2016)
The α-crystallin domain (ACD) is an ancient domain conserved among all kingdoms. Plant ACD proteins have roles in abiotic stresses, transcriptional regulation, inhibiting virus movement and DNA demethylation. An exhaustive in-silico analysis using Hidden Markof Model-based conserved motif search of the tomato proteome yielded a total of 50 ACD proteins that belonged to 4 groups, sub-divided further into18 classes. One of these groups belongs to the small heat shock protein (sHSP) class of proteins, molecular chaperones implicated in heat tolerance. Both tandem and segmental duplication events appear to have shaped the expansion of this gene family with purifying selection being the primary driving force for evolution. The expression profiling of the Acd genes in two different heat stress regimes suggested that their transcripts are differentially regulated with roles in acclimation and adaptive response during recovery. The co-expression of various genes in response to different abiotic stresses (heat, low temperature, dehydration, salinity and oxidative stress) and phytohormones (abscisic acid and salicylic acid) suggested possible cross-talk between various members to combat a myriad of stresses. Further, several genes were highly expressed in fruit, root and flower tissues as compared to leaf signifying their importance in plant development too. Evaluation of the expression of this gene family in field grown tissues highlighted the prominent role they have in providing thermo-tolerance during daily temperature variations. The function of three putative sHSPs was established as holdase chaperones as evidenced by protection to malate-dehydrogenase against heat induced protein-aggregation. This study provides insights into the characterization of the Acd genes in tomato and forms the basis for further functional validation in-planta.